Comparative Analysis of SVM and CNN for Pneumonia Detection in Chest X-Ray - Saraswati, Ni Wayan Sumartini; Dewi, Dewa Ayu Putu Rasmika; Pirozmand, Poria (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 15 No 1 (2024): Vol. 15, No. 1 April 2024DO - 10.24843/LKJITI.2024.v15.i01.p04, 2024)
Recognizing pneumonia sufferers can be done by analyzing chest X-ray images. Pneumonia sufferers experience pleural effusion, where fluid is between the lungs’ layers. It causes the lungs’ X-ray picture to be cloudy or hazy. It differs from the appearance of X-rays on normal lungs which are dark in color. These differences in X-Ray images can be classified automatically with the help of Artificial Intelligence This research used convolutional neural networks and support vector machine methods to recognize X-ray images of pneumonia. This research applied Principal Component Analysis and Wavelet Transformation support to both methods. This research aimed to evaluate the performance of each model combination. The PCA-SVM model gave the best performance, with an accuracy of 94.545% and an F1 score of 94.675%. The SVM model outperforms the CNN model in recognizing images; in this case, it could be due to the relatively small amount of training data.